The effect of irrigation on the yield and quality of maize (Zea mays L.) hybrids - Virág, István Csaba; Vad, Attila Miklós; Kutasy, Erika Tünde (Acta Agraria Debreceniensis, 2020)
In this study, the effect of water supply on the quality and productivity of different maize hybrids was observed.Maize production is influenced by many agro-technical factors such as nutrient supply, plant density, environmental factors, water supply and temperature. Good soil quality and adequate technology significantly reduce the unfavourable effect of crop year. The impact of fertilization, crop rotation, irrigation and plant density on maize yield was greatly affected by crop year and crop rotation. The main constituent (69–75% dry matter concentration) of maize seed is starch, however, its increase can be achieved only to a limited extent, as increasing the starch content will reduce other parameters, especially protein content. Significant nutrient content improvements can be achieved by appropriate hybrid-site connection and the use of adequate technology. Protein content reduction with optimal water supply can be positively influenced by the appropriate nutrient supply for the hybrid.The experiments were carried out at the Látókép Experimental Site of Crop Production on calcareous chernozem soil. The weather of the examined year, which was partly favorable for maize and partly unfavourable in other respects, was also reflected in the development of maize and yields achieved.In 2019, we were examining the hybrids of Kamaria (FAO 370), P 9903 (FAO 390), DKC 4351 (FAO 370) and KWS Kamparis (FAO 350–400). Due to the dry soil condition, sowing was delayed, however, the hybrids emerged ideally because rain arrived soon after sowing, which facilitated initial development. Young plants evolved rapidly and dynamically in the case of all hybrids. In terms of heat-demanding bread, the month of May was unfavourable to temperatures below the annual average, but the higher amount rainfall helped the development. However, due to the drier period in early July, 25–25 mm of irrigation water was applied to half of the experimental areas on July 1 and 15.The aim of our research was to determine the best population density for hybrids under favourable soil conditions (calcareous chernozem soil). In both irrigated and dry conditions, a crop density of 75,000 crops were the most favourable for the Kamaria hybrid. The P9903 hybrid in the case of a crop density of 85 crops proved to be ideal and the DKC4351 had an optimal population density of 95,000.However, it should be taken into consideration that, in the case of soils with poor water management, the drought sensitivity of the crop stand may increase at a population density of 95,000.As a result of irrigation, yield increased and the difference between the examined plant numbers decreased. The yield growth was relatively moderate (341 kg ha-1 – 1053 kg ha-1), which makes the economicalness of irrigation doubtful in the given year.